Mengenal Relasi dalam Matematika : Pengertian, Cara Penyajian, Sifat - Sifat, dan Contoh Penerapannya (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Relations in mathematics are a fundamental concept that describe the connection between two sets. This concept is crucial because it forms the foundation for understanding functions and various other mathematical topics. In everyday life, relations can be found in numerous real-world situations, such as the relationship between teachers and their students, sellers and buyers, or students and their exam scores. By understanding relations, students can see how elements from one set are linked to elements in another set based on specific rules. Unfortunately, many students still find it difficult to grasp the concept of relations because it is often taught in an abstract way, filled with mathematical symbols that are not connected to their real-life experiences. As a result, students may feel that the topic is irrelevant to their lives, leading to a lack of interest and poor comprehension. In fact, if taught contextually and practically, the concept of relations can serve as a key bridge to help students understand functions and their relevance in the real world. This article aims to explain the concept of relations through a more practical and relatable approach. For example, it can be illustrated by connecting students' names with their attendance numbers, or linking foods with their nutritional contents. Through these examples, students can see that relations are not just rigid parts of a math lesson but also reflect meaningful connections in everyday life. In this way, it is expected that students will gain a more comprehensive understanding of relations—not only mathematically but also in terms of practical application and functionality. A solid understanding of relations will make it easier for students to learn advanced concepts such as functions, mappings, and mathematical logic. Therefore, a learning approach that emphasizes contextual understanding is essential, so that students are not merely memorizing formulas but are also capable of applying the concept of relations in real-world situations.